Bidirectional crosstalk between the peripheral nervous system and lymphoid tissues/organs - Boahen, Angela; Hu, Dailun; Adams, Murray J.; Nicholls, Philip K.; Greene, Wayne K.; Ma, Bin (Frontiers in Immunology, 2023)
The central nervous system (CNS) influences the immune system generally by regulating the systemic concentration of humoral substances (e.g., cortisol and epinephrine), whereas the peripheral nervous system (PNS) communicates specifically with the immune system according to local interactions/connections. An imbalance between the components of the PNS might contribute to pathogenesis and the further development of certain diseases. In this review, we have explored the "thread" (hardwiring) of the connections between the immune system (e.g., primary/secondary/tertiary lymphoid tissues/organs) and PNS (e.g., sensory, sympathetic, parasympathetic, and enteric nerve systems (ENS)) in health and disease in vitro and in vivo.Neuroimmune cell units provide an anatomical and physiological basis for bidirectional crosstalk between the PNS and the immune system in peripheral tissues, including lymphoid tissues and organs. These neuroimmune interactions/modulation studies might greatly contribute to a better understanding of the mechanisms through which the PNS possibly affects cellular and humoral-mediated immune responses or vice versa in health and diseases. Physical, chemical, pharmacological, and other manipulations of these neuroimmune interactions should bring about the development of practical therapeutic applications for certain neurological, neuroimmunological, infectious, inflammatory, and immunological disorders/diseases.